Telehealth nursing interventions for phenotypes of older adults with COPD: an exploratory study - Arnaert, A.; Ahmed, A.M.I.; Debe, Z.; Charbonneau, S.; Paul, S. (Frontiers in Digital Health, 2023)
Inconclusive results exist around the effectiveness of telemonitoring for patients with COPD, and studies recommended conducting subgroup analyses to identify patient phenotypes that could benefit from these services. This exploratory study investigated what type of COPD patients were receiving which type of telenursing interventions more frequently using the telemonitoring platform. A sample of 36 older adults with COPD were receiving telenursing services for 12 months and were asked to answer five COPD-symptom related questions and submit their vital signs daily. Findings revealed two phenotypes of older adults for whom the frequency of telenursing calls and related interventions differed. Although no statistically significant differences were observed in participants' GOLD grades and hospitalizations, cluster one participants used their COPD action plan significantly more frequently, and were in frequent contact with the telenurse. It is paramount that further research is needed on the development of patient phenotypes who may benefit from telemonitoring.